The use of PPE Against the Incidence of COVID-19 Infection on Indonesian Healthcare Workers - Maria Ulfa; Momoyo Azuma; Dayu Laras Wening; Ahmad Veda Yudanto (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2021)
As the front-liner in handling the spread of COVID-19, healthcare workers are a susceptible group toward the exposure of SARS-CoV-2. This study aims to examine the compliance of PPE use by health workers, FFRs reuse, the participation of healthcare workers in infection and prevention training, and the relationship between mentioned variables and COVID-19 infection among healthcare workers. This research was conducted with a quantitative approach through a retrospective cohort design. Respondents in this study were the healthcare workers throughout Indonesia who worked actively during the pandemic in healthcare facilities. This study found that the level of compliance of PPE use among healthcare workers was high. The groups who reuse masks are mostly doctors and nurses and the most widely used method of disinfection is UVC radiation. Some of the respondents were recorded for being attended the infection and prevention training. However, there is no correlation between adherence to wearing PPE, reuse of masks, and infection prevention training with COVID-19 infection in health workers in Indonesia (r=0.02; p=0.5).